Pivotal Role of Adenosine Neurotransmission in Restless Legs Syndrome - Ferré, Sergi; Quiroz, César; Guitart, Xavier; Rea, William; Seyedian, Arta; Moreno, Estefanía; Casadó-Anguera, Verònica; Díaz-Ríos, Manuel; Casadó, Vicent; Clemens, Stefan; Allen, Richard P.; Earley, Christopher J.; et al. (Frontiers in Neuroscience, 2018)
The symptomatology of Restless Legs Syndrome (RLS) includes periodic leg movements during sleep (PLMS), dysesthesias and hyperarousal. Alterations in the dopaminergic system, a presynaptic hyperdopaminergic state, seem to be involved in PLMS, while alterations in glutamatergic neurotransmission, a presynaptic hyperglutamatergic state, seem to be involved in hyperarousal and also PLMS. Brain iron deficiency (BID) is well recognized as a main initial pathophysiological mechanism of RLS. BID in rodents have provided a pathogenetic model of RLS that recapitulates the biochemical alterations of the dopaminergic system of RLS, although without PLMS-like motor abnormalities. On the other hand, BID in rodents reproduce the circadian sleep architecture of RLS, indicating the model could provide clues for the hyperglutamatergic state in RLS. We recently showed that BID in rodents is associated with changes in adenosinergic transmission, with downregulation of adenosine A1 receptors (A1R) as the most sensitive biochemical finding. It was hypothesized that A1R downregulation leads to hypersensitive striatal glutamatergic terminals and facilitation of striatal dopamine release. Hypersensitivity of striatal glutamatergic terminals was demonstrated by an optogenetic-microdialysis approach in the rodent with BID, indicating that it could represent a main pathogenetic factor that leads to PLMS in RLS. In fact, the dopaminergic agonists pramipexole and ropinirole and the α2δ ligand gabapentin, used in the initial symptomatic treatment of RLS, completely counteracted optogenetically-induced glutamate release from both normal and BID-induced hypersensitive corticostriatal glutamatergic terminals. It is a main tenet of this essay that, in RLS, a single alteration in the adenosinergic system, downregulation of A1R, disrupts the adenosine-dopamine-glutamate balance uniquely controlled by adenosine and dopamine receptor heteromers in the striatum and also the A1R-mediated inhibitory control of glutamatergic neurotransmission in the cortex and other non-striatal brain areas, which altogether determine both PLMS and hyperarousal. Since A1R agonists would be associated with severe cardiovascular effects, it was hypothesized that inhibitors of nucleoside equilibrative transporters, such as dipyridamole, by increasing the tonic A1R activation mediated by endogenous adenosine, could represent a new alternative therapeutic strategy for RLS. In fact, preliminary clinical data indicate that dipyridamole can significantly improve the symptomatology of RLS.